Concentrations and deficiencies of minerals in cattle submitted to a diagnostic laboratory in Saskatchewan from 2003–2012: A retrospective study - Perdrizet, Ursula (Can Vet J, 2020)
Trace mineral analyses of samples submitted to Prairie Diagnostic Services laboratory from Saskatchewan cattle between 2003 and 2012 were examined, with the objective of describing trends and reporting concentrations and deficiencies of minerals. Deficiencies were observed with copper, iron, manganese, magnesium, zinc, and cobalt. Deficiency was most commonly seen in copper, followed by iron, manganese, and magnesium accounting for 47.2%, 15.1%, 13.0%, and 10.8% of deficiencies, respectively. Deficiency in cobalt was least common followed by zinc accounting for 4.2% and 9.7% of deficiencies, respectively. The following minerals were also analyzed: barium, beryllium, bismuth, cadmium, chromium, antimony, tin, molybdenum, strontium, thallium, and vanadium. Submissions from 1434 animals were reviewed and a diagnosis of mineral deficiency was made for 509 animals with 92 of these having multiple deficiencies. There were significant differences in the number of deficient animals by year (P = 0.001), age group (P = 0.01), but not month (P = 0.109) or soil type (P = 0.172).